8-node hexahedron hybrid element based on ABAQUS - Li Hao; Xiao Ru Cheng; Yao Yuntao (2011 International Conference on Electric Technology and Civil Engineering, 2011)
An 8-node hexahedron hybrid stress element is developed by using the user element interface(UEL) in ABAQUS. ABAQUS element library are expanded. The 8-node hexahedron hybrid stress element is based on the modified Hellinger-Reissner variation principle with non-conforming displacement functions. The element can be used in 3-D finite element analysis of straight box girders .The numerical example indicate that the hybrid stress element can get good result in the finite element analysis under coarse mesh. The feasibility and validity of the interface subroutine has also been proved.